2022
DOI: 10.3390/ijms231710026
|View full text |Cite
|
Sign up to set email alerts
|

Disorder of Sex Development Due to 17-Beta-Hydroxysteroid Dehydrogenase Type 3 Deficiency: A Case Report and Review of 70 Different HSD17B3 Mutations Reported in 239 Patients

Abstract: The 17-beta-hydroxysteroid dehydrogenase type 3 (17-β-HSD3) enzyme converts androstenedione to testosterone and is encoded by the HSD17B3 gene. Homozygous or compound heterozygous HSD17B3 mutations block the synthesis of testosterone in the fetal testis, resulting in a Disorder of Sex Development (DSD). We describe a child raised as a female in whom the discovery of testes in the inguinal canals led to a genetic study by whole exome sequencing (WES) and to the identification of a compound heterozygous mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Genomic deoxyribonucleic acid (DNA) was extracted from the peripheral blood leukocytes of each patient and used for WES analysis according to previously described methods (12). A virtual gene panel was created, consisting of 29 genes in which germline or mosaic mutations have been reported in patients with familial isolated or syndromic pituitary adenomas (46), namely AIP (NM_003977.3), CABLES1 (NM_001100619.2), CDH23 (NM_022124.5), CDKN1A (NM_078467.3), CDKN1B (NM_004064.4), CDKN2B (NM_004936.4), CDKN2C (NM_001262.3), DICER1 (NM_177438.3) , GNAS (NM_000516.7) , GPR101 (NM_054021.1) , MAX (NM_002382) , MEN1 (NM_130799.2) , MLH1 (NM_000249.4), MSH2 (NM_000251.3) , MSH6 (NM_000179.3) , NF1 (NM_000267.3) , PMS2 (NM_000535.7), PRKACA (NM_002730.4), PRKACB (NM_182948.4) , PRKAR1A (NM_002734.5) , RET (NM_020975.4) , SDHA (NM_004168.3) , SDHAF2 (NM_017841.2) , SDHB (NM_003000.3) , SDHC (NM_003001.5) , SDHD (NM_003002.3) , TP53 (NM_000546.6), USP8 (NM_005154.5), and VHL (NM_000551.3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic deoxyribonucleic acid (DNA) was extracted from the peripheral blood leukocytes of each patient and used for WES analysis according to previously described methods (12). A virtual gene panel was created, consisting of 29 genes in which germline or mosaic mutations have been reported in patients with familial isolated or syndromic pituitary adenomas (46), namely AIP (NM_003977.3), CABLES1 (NM_001100619.2), CDH23 (NM_022124.5), CDKN1A (NM_078467.3), CDKN1B (NM_004064.4), CDKN2B (NM_004936.4), CDKN2C (NM_001262.3), DICER1 (NM_177438.3) , GNAS (NM_000516.7) , GPR101 (NM_054021.1) , MAX (NM_002382) , MEN1 (NM_130799.2) , MLH1 (NM_000249.4), MSH2 (NM_000251.3) , MSH6 (NM_000179.3) , NF1 (NM_000267.3) , PMS2 (NM_000535.7), PRKACA (NM_002730.4), PRKACB (NM_182948.4) , PRKAR1A (NM_002734.5) , RET (NM_020975.4) , SDHA (NM_004168.3) , SDHAF2 (NM_017841.2) , SDHB (NM_003000.3) , SDHC (NM_003001.5) , SDHD (NM_003002.3) , TP53 (NM_000546.6), USP8 (NM_005154.5), and VHL (NM_000551.3).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic deoxyribonucleic acid (DNA) was extracted from the peripheral blood leukocytes of each patient and used for WES analysis according to previously described methods (12). A virtual gene panel was created, consisting of 29 genes in which germline or mosaic mutations have been reported in patients with familial isolated or syndromic pituitary adenomas (4-6), namely…”
Section: Whole Exome Sequencing (Wes) and Virtual Gene Panelmentioning
confidence: 99%
“…HSD17B3 deficiency is the most common disorder of androgen synthesis, with 70 reported mutations in humans that result in a disorder of sexual development (DSD) phenotype [ 21 , 22 ]. This disorder is caused by a genetic mutation in the HSD17B3 gene and results in perturbed sexual differentiation in males as it prevents the sufficient reduction of androstenedione into testosterone.…”
Section: Human Hsd17b3 Deficiencymentioning
confidence: 99%
“…HSD17B3 has long been thought to be the main testosterone biosynthetic enzyme in adult males and required for sexual development and fertility. HSD17B3 loss-of-function mutations in humans results in perturbed male sexual differentiation [ 22 ], however, recent ground-breaking studies have revealed that ablation of the canonical pathway in transgenic mice deficient in HSD17B3, has little impact on male development and fertility [ 17 , 34 ]. These HSD17B3 KO mouse models demonstrate the presence of species differences in androgen production and highlight the challenges that scientists experience when trying to study human disorders.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%
“…This gene encodes a 310-amino acid protein spanning 11 exons and 10 introns ( 3 ). To date, a total of 70 distinct HSD17B3 mutations have been identified, encompassing various types such as missense mutations (the most prevalent), splice-site mutations, minor deletions, and insertions, among others ( 4 ). These mutations invariably result in the loss of functionality in the 17β-HSD3 protein, which plays a vital role in the production of sex hormones critical for male sexual development and reproduction ( 5 ).…”
Section: Introductionmentioning
confidence: 99%